Pengaruh Pemanfaatan Media Sosial Instagram @Infosumbar Terhadap Kepuasan Memperoleh Informasi Masyarakat Kota Padang (Studi Pada Pengikut Instagram @Infosumbar) - Ayu Lestari; Zike Martha (CV. ITTC INDONESIA, 2026)
This study aims to determine the effect of the use of Instagram social media @infosumbar on the satisfaction of obtaining information in Padang City residents, using the Uses and Gratification theory for this utilization covering information, Personal, Social Interaction, and Entertainment. This study used a quantitative approach with 100 respondents who are followers of the Instagram account @infosumbar and who are domiciled in Padang City. The results of this study indicate a significant influence, it is known that respondents in this study have a fairly high level of satisfaction in obtaining information, more than 60% of respondents are satisfied with the information presented by the Instagram account @infosumbar with a concise presentation of information and the speed of updates of information that makes respondents in this study have a high level of satisfaction.